Scaling Community-Based Breeding Programs: Empowering Youth and Extension Experts for Commercialization of Small Ruminant Production - Belay, Berhanu; Getachew, Tesfaye; Haile, Aynalem (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
Small ruminants, particularly sheep, are the major contributors in the livelihood of smallholder livestock keepers in Menz Gera Midir district. Menz sheep are small-sized, have a lower mature weight, and have poor reproductive efficiency. However, they are adaptive to breed in cold and feed scarce areas. To improve Menz sheep's productivity, a community-based breeding program was initiated by ICARDA and parents in 2009 as an alternative breed improvement program. Over the years, genetic improvement practices and management practices have helped produce bundled technologies and innovations to enhance productivity. There was also pressing interest in scaling up the innovations to reach more smallholder farmers and benefit from the improved and bundled technology. A scaling framework comprising CBBP, PU, finishers, and market access was developed for complementary implementation. The implementation of the scaling framework followed a cluster approach that extends the technology from pilot to breed-level improvement. Gera Mider Woreda was selected to represent 887 and 300 finishers in 10 rural and 5 small town villages engaged in finishing to put a complementary scaling framework on the ground. The training workshop was organized for two days and constituted 28 / 4 women and 24 men/ participants drawn from research, extension, cooperatives, trade and commerce, and the practitioners of finishing with the aim of developing a model scaling framework that would be scaled up to other regions. The workshop content includes SmaRT pack and business development with a modality of group discussion and experience sharing. The training offered will reach the community and multiple stakeholders in the district. The training was concluded through an action plan that identified the main actors, the activities, and the timeline, with built-in monitoring and evaluation.